Ղազարոս Սարյան. ուսուցիչս եվ բարեկամս - Նորայրի Մարկոսյան, Արա (Musical Armenia, 2010)
Conductor of the Moscow Opera Theatre after Pokrovsky, Associate Professor Ara Norair Markosian inmemory analytical article “Lazar Saryan: my teacher and friend” being a student conductor of Yerevan State Conservatory after Komitas shows the teacher as a righteous man, a wonderful teacher and expert in the subject of “Instrumentology.” Also describes the friendship with the teacher after graduation and his role in the future and as rector of YSC.